The high costs of conserving Southeast Asia's lowland rainforests. Issue 6 (3rd February 2011) - Fisher, Brendan; Edwards, David P; Giam, Xingli; Wilcove, David S
Abstract : Mechanisms that mitigate greenhouse‐gas emissions via forest conservation have been portrayed as a cost‐effective approach that can also protect biodiversity and vital ecosystem services. However, the costs of conservation – including opportunity costs – are spatially heterogeneous across the globe. The lowland rainforests of Southeast Asia represent a unique nexus of large carbon stores, imperiled biodiversity, large stores of timber, and high potential for conversion to oil‐palm plantations, making this region one where understanding the costs of conservation is critical. Previous studies have underestimated the gap between conservation costs and conversion benefits in Southeast Asia. Using detailed logging records, cost data, and species‐specific timber auction prices from Borneo, we show that the profitability of logging, in combination with potential profits from subsequent conversion to palm‐oil production, greatly exceeds foreseeable revenues from a global carbon market and other ecosystem‐service payment mechanisms. Thus, the conservation community faces a massive funding shortfall to protect the remaining lowland primary forests in Southeast Asia.